Genetic variability of Colocasia esculenta (L.) Schott. - Paul, KK; Bari, MA; Debnath, SC (Bangladesh Journal of Botany, 2012)
Studies on the nature and extent of variability of aqua edible aroids cultivars, Colocasia esculenta (L.) Schott. revealed significant differences and wide range of variations among the accessions and cultivars. Genotypic variances and coefficient of variation for most of the characters were remarkably higher than their corresponding variances due to environment which also indicate the existence of variation in genotypic origin. Plant height, petiole length, leaf length, each stolon weight, total stolon weight, stolon length and corm length expressed high heritability with moderate to high genetic advance signaled heritable in nature. Key words: Genetic variability; Heritability; Colocasia esculenta; Genetic advance DOI: http://dx.doi.org/10.3329/bjb.v40i2.9775 Bangladesh J. Bot. 40(2): 185-188, 2011 (December)